“No Poor Among Them” Sabbath and Jubilee Years in Lukan Social Ethics - Smith, David Andrew (2018)
This article examines the reconfiguration of socially poignant Pentateuchal texts in Luke-Acts. Beginning with a critical examination of the Jubilee background of Jesus’ Nazareth sermon, the article moves to elucidate Luke’s interweaving of scriptural traditions of the Jubilee and Sabbath years and related economically rich scriptural texts into the story of Jesus and the early church. This study explores how the author of Luke and Acts has integrated the life and teachings of Jesus with the kerygma and social existence of the early church by way of sustained, subtle reference to idealized visions of communal life in Israel’s foundational scriptures.
Keywords: Luke -- Acts -- Jubilee -- Sabbath -- intertextuality -- ethics -- economics -- theology